Enhancing cross-cultural well-being: a mixed methods study on critical thinking, cultural intelligence, and eudaimonic well-being in arts students’ cultural identity development - Peng, Yue (Frontiers in Psychology, 2024)
Introduction This research explores the role of critical thinking and cultural intelligence in psychological well-being through the lens of cultural identity development. It aims to understand how individuals think critically and navigate different cultural challenges that influence their psychological wellbeing. Methods The quantitative analysis utilizes various scales to elucidate the correlation between critical thinking beliefs, cultural intelligence, and well-being. The qualitative exploration employing NVivo 20.0 uncovers the interplay between critical thinking, cultural intelligence, and well-being in the construction of cultural identity and psychological selfhood. Results The research results show a significant positive correlation between critical thinking, cultural intelligence, and psychological well-being. Themes such as well-being, cultural intelligence, critical thinking, and facing challenges illustrate how individuals navigate obstacles to achieve a meaningful and purposeful life. The findings from both the quantitative and qualitative analyses provide a comprehensive understanding of how critical thinking, cultural intelligence, and well-being intersect and influence individuals’ perceptions of themselves and their cultural identities. Discussion The research results suggest that developing critical thinking and cultural intelligence positively impacts individuals’ psychological well-being in cultural identity development. This can lead to greater belonging and acceptance in diverse cultural settings.